Avoiding anti-inflammatories: a randomised controlled trial testing the effect of an eHealth information package on primary healthcare patient medication knowledge and behaviour in Aotearoa New Zealand - Leitch, Sharon; Zeng, Jiaxu; Smith, Alesha; Stokes, Tim (BMJ open, 2024)
BackgroundPatient medication knowledge and health literacy affect patient safety. Taking angiotensin-converting enzyme inhibitors (ACE-i) or angiotensin II receptor blockers (ARBs), with diuretics and non-steroidal anti-inflammatory medications (NSAIDs) is nephrotoxic. Patients may not know of this risk. An eHealth information package was developed to inform patients at risk of taking this combination of medication.ObjectiveTo assess the impact of the eHealth information package on patient knowledge and behaviour.DesignThis was a two-arm, parallel, randomised control trial. A knowledge quiz and NSAID use survey were undertaken at baseline, and repeated after two weeks. The intervention group accessed the information package after completing the baseline assessment. The control group received normal care.Setting and participantsPrimary healthcare patients prescribed an ACE-i or ARB plus a diuretic in Aotearoa New Zealand.InterventionA novel eHealth information package was made available to participants in the intervention group consisting of a downloadable PDF and online education activity. This took approximately 15 min for participants to complete.Primary outcome measuresChange in knowledge scores and in NSAID use between pre-intervention and post-intervention assessment.Secondary outcome measuresSelf-reported patient intentions regarding future NSAID useResultsThe 201 participants who completed the study had high baseline NSAID medication knowledge, which did not substantially change at follow-up. The intervention group had a 0.35 (95% CI: -0.18, 0.88) higher knowledge score than the control group. NSAID use decreased over the study; the intervention group had 62% lower odds of NSAID use at follow-up assessment compared with the control group (OR=0.37, 95% CI: 0.14, 1.03). There was no substantial difference between study groups at follow-up for self-reported action. The information package was considered acceptable and useful.ConclusionThis tailored eHealth information package may reduce NSAID use in patients at increased risk from NSAID-related harm.Trial registration numberAustralian New Zealand Clinical Trial Registry (ACTRN:12622001132730).